2023
DOI: 10.3390/w15020336
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Mapping of Groundwater Potentiality Applying Geometric Average and Fractal Models: A Sustainable Approach

Abstract: Water scarcity affects all continents, with approximately 1.2 billion people living in areas where water is physically lacking. This scarcity is more accentuated in countries with an arid climate, and its impact becomes more threatening when the economy depends mainly on it. The Kingdom of Morocco, with its agricultural vocation, is one of them, especially in its southern regions. Therefore, mapping areas with high groundwater potential based on available geospatial data allows for optimizing the choice of a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 102 publications
2
16
0
Order By: Relevance
“…In this study, we use the AHP model with 14 factors to map the potential groundwater areas (GWPA) in the Ifni basin. This approach has yielded satisfactory results in similar basins [4,5,9,11,19,22]. Our analysis of the factors, such as those used in previous studies [4,5,10,22], revealed that certain relevant factors, such as land use, the intersection between geological lineaments and the hydrographic network, the density of the nodes, and TPI, were not considered in the model.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…In this study, we use the AHP model with 14 factors to map the potential groundwater areas (GWPA) in the Ifni basin. This approach has yielded satisfactory results in similar basins [4,5,9,11,19,22]. Our analysis of the factors, such as those used in previous studies [4,5,10,22], revealed that certain relevant factors, such as land use, the intersection between geological lineaments and the hydrographic network, the density of the nodes, and TPI, were not considered in the model.…”
Section: Introductionmentioning
confidence: 78%
“…This approach has yielded satisfactory results in similar basins [4,5,9,11,19,22]. Our analysis of the factors, such as those used in previous studies [4,5,10,22], revealed that certain relevant factors, such as land use, the intersection between geological lineaments and the hydrographic network, the density of the nodes, and TPI, were not considered in the model. In discontinuous environments, aquifer recharge primarily occurs through faults and lineaments that intersect with the hydrographic network [34].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…From documented reports, the groundwater potential zones have been defined and mapped using various techniques. For instance, some researchers have used probabilistic models like the frequency ratio (Ozdemir 2011;Razandi et al, 2015), logistic regression (Ozdemir 2011;Pourtaghi and Pourghasemi 2014;Pourghasemi and Beheshtirad, 2015), weights of evidence (Corsini et al, 2009;Ozdemir 2011;Lee et al, 2012;Echogdali et al, 2023), evidential belief function (Mogaji et al, 2015;Pourghasemi and Beheshtirad, 2015), certainty factor (Razandi et al, 2015), decision tree (Chenini and Mammou 2010), artificial neural network model (Lee et al, 2012), Shannon's entropy (Naghibi et al, 2015), on the whole, remote sensing and GIS are powerful tools that can quickly estimate natural resources. The methods are affordable and can be utilized to successfully explore groundwater (Faust et al, 1991;Hinton 1996;Jha et al, 2010;Benjmel et al, 2022) before utilizing more involved and expensive surveying techniques.…”
Section: Introductionmentioning
confidence: 99%